Variational Formulation with Deviating Arguments of Movable boundaries - Baghdad Science Journal (مجلة بغداد للعلوم)
In this paper, we study, in details the derivation of the variational formulation corresponding to functional with deviating arguments corresponding to movable boundaries. Natural or transversility conditions are also derived, as well as, the Eulers equation. Example has been taken to explain how to apply natural boundary conditions to find extremal of this functional.